Finding the way to God through folk songs in Banyumasan, Indonesian, and English versions of Ahmad Tohari’s Bekisar Merah - Romala, Almira Ghassani Shabrina (Universitas Sanata Dharma, 2023)
As a part of cultural heritage and identity, folk songs can also be found in literary works and their translations. As they often contain cultural references and expressions specific to a particular community, these elements can be complex to translate without losing their cultural significance or meaning. Therefore, to answer this problem, this research aims to identify and explain the strategies employed in rendering the Banyumasan folk songs to Indonesian and English in Ahmad Tohari’s Bekisar Merah and its English translation, The Red Bekisar, utilizing Baker’s classification of translation strategies, i.e., cultural substitution, paraphrase using a related word, superordinate, loan word plus explanation, less expressive word, paraphrase using unrelated words, omission, and illustration. This research is conducted through a descriptive qualitative approach, with the folk songs collected through document analysis utilizing content and thematic analysis. In the Indonesian and English versions of the folk songs, the translators render the Banyumasan culture-specific items in the songs into more general words, neutral and less expressive words, cultural substitution, paraphrasing using related words, and omission in the attempt to achieve both communicative and culturally appropriate translation. It is expected that exploring the strategies for translating folk songs will contribute both to academicians and practitioners, as well as literary translators, in ensuring accurate translation, cultural sensitivity, preserving authenticity, and achieving the communication goals of the traditional folk songs to a global audience.